A study on the correlation of care knowledge, behavior, self-efficacy and care burden of informal nursing staff in community elderly with long-term bed rest and s kin pressure injuries (长期卧床伴皮肤压力性损伤的社区老年人非正式护理人员的照顾知识、行为、自我效能及照顾负担的相关性研究) - JIANG Yanqin (蒋燕勤); ZHU Zhu (朱珠); WANG Jing (王静); SONG Ailin (宋爱琳); WANG Guixia (汪桂霞); ZHU Qunmei (朱群妹); LUAN Wei (栾伟) (中西医结合护理)
Objective To understand the knowledge, skill status, general self-efficacy and the correlation of care burden of community elderly patients with skin pressure injuries and their informal caregivers. Methods A total of 280 community elderly informal nurses from 8 tertiary hospitals, 1 community hospital and 1 social medical institution in Shanghai were assessed with general information, knowledge questionnaire, behavior questionnaire, General Self-Efficacy Scale and Caregiver Burden Scale. Results The average score of informal nursing staff's care knowledge and behavior was (17. 25±2. 90) and (35. 27±6. 82) respectively, and the score of self-efficacy was (2. 33±0. 61). The score of caregiver's burden was relatively high ( 65. 12±14. 93). The general self-efficacy of caregivers on pressure injuries was positively correlated with the total score and all dimensions of care behavior (P＜0. 001). The general self-efficacy and co- caregivers, development limitation, emotional burden, average time spent caring for patients every day and caregiver knowledge questionnaire score were the influencing factors of care behavior of pressure injuries. Conclusion The level of nursing knowledge and behavior of informal nursing staff needs to be improved, the level of self-efficacy is general, and the burden of care is heavy. It is suggested to improve their knowledge, skills, behavior and self-efficacy from various aspects, the ultimate goal of promoting the healing and reducing the recurrence of stress injury of the community elderly is to build up the confidence of coping with care work. (目的 了解长期卧床伴皮肤压力性损伤的社区老年患者及其非正式护理人员主要照顾者的知识、技能现状、一般自我效能及照顾负担的相关性。方法 对上海8家三级医院、1家社区医院、1家社会办医机构合计280位长期卧床社区老年人及其非正式护理人员进行一般资料、压力性损伤的知识问卷、行为问卷、一般自我效能量表及照顾者负担量表的测评。结果 非正式护理人员照顾知识及行为得分平均分情况为(17. 25±2. 90)分及(35. 27±6. 82)分, 自我效能得分为(2. 33±0. 61)分; 照顾者负担得分较高为(65. 12±14. 93)分; 照顾者压力性损伤一般自我效能与照顾行为总分及各维度均呈现显著正相关(P＜0. 001); 一般自我效能、是否有共同照顾者、发展受限性、情感性负担、平均每天照顾患者耗时及照护者知识问卷得分6个变量是压力性损伤照顾行为的影响因素。结论 非正式护理人员照顾知识及行为水平有待提高, 自我效能水平一般, 照顾负担较重。建议从多种方面入手, 提高其知识技能行为水平及自我效能水平, 树立起应对照顾工作的信心, 从而达到促进社区老年人压力性损伤愈合及降低再发生情况的最终目标。)